Perfluoroarene-based peptide macrocycles that inhibit the Nrf2/Keap1 interaction - Steel, Richard J.; O'Connell, Maria A.; Searcey, Mark (Bioorganic & medicinal chemistry letters, 2018)
[Display omitted] The Nrf2/Keap1 interaction is a target in the development of new therapeutic agents, where inhibition of the interaction activates Nrf2 and leads to the generation of downstream anti-inflammatory effects. Peptides that mimic the β-turn in the Keap1 active site and are constrained by a disulfide bridge have high affinity for Keap1 but no intracellular activity. The introduction of a perfluoroalkyl-bridging group to constrain the peptides, coupled with a glutamic acid to proline replacement leads to a new peptide with a Ki of 6.1 nM for the Nrf2/Keap1 binding interaction, although this does not translate into intracellular activity.